2011
DOI: 10.1111/j.1442-200x.2010.03285.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower respiratory tract infections and gastrointestinal infections among mature babies in Japan

Abstract: One out of 11 children was hospitalized because of LRTI or GII during their first 18 months, which was associated with a biologic factor (sex), environmental factors (child-care attendance and family size), and parenting practices (shorter duration of exclusive breast-feeding and caregivers' unfavorable hygiene practices).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…However, the qualitative analysis of both parenting counseling records and discussion notes from PHNs’ training workshops, although limited in amount and time-frame, can provide comprehensive information for PHNs and policy makers to understand community needs and to formulate appropriate strategies. Of note, a comparison between the present study and a previous study adopting a similar sampling strategy throughout a year in the sample city has indicated no differences in mothers and children’s basic characteristics [ 32 ].…”
Section: Discussionmentioning
confidence: 55%
“…However, the qualitative analysis of both parenting counseling records and discussion notes from PHNs’ training workshops, although limited in amount and time-frame, can provide comprehensive information for PHNs and policy makers to understand community needs and to formulate appropriate strategies. Of note, a comparison between the present study and a previous study adopting a similar sampling strategy throughout a year in the sample city has indicated no differences in mothers and children’s basic characteristics [ 32 ].…”
Section: Discussionmentioning
confidence: 55%
“…Former studies mostly examined the admission rates of specific subtypes of infections in pediatric patients [5][6][7][8] and fewer examined admission rates for all infections [2][3][4]. Most studies focused on children below 5 years of age, those including older children often grouped young and older children together [2][3][4]9].…”
Section: Introductionmentioning
confidence: 99%
“…One paper from Germany reported that a longer duration of EBF led to a higher risk of ARI [ 37 ]. All studies assessing lower respiratory tract infections ( n = 6), pneumonia ( n = 5), bronchiolitis ( n = 1), and broad respiratory/chest infections ( n = 5) reported a protective association with EBF [ 11 , 18 , 21 , 28 , 32 , 33 , 34 , 35 , 39 , 40 , 41 , 48 , 49 , 50 , 56 , 57 , 79 ]. A few studies found that there was no significant association between EBF and tuberculosis ( n = 1), upper respiratory tract infection ( n = 1), and pertussis ( n = 1) [ 44 , 52 , 61 ].…”
Section: Resultsmentioning
confidence: 99%